Conservation of vaccines in basic health units: diagnostic analysis in the municipalities mineiros - Valéria Conceição de Oliveira; Eliete Albano de Azevedo Guimarães; Suelem Santos Silva; Ione Carvalho Pinto (Universidade Federal do Ceará, 2012)
Vaccines are thermo labile products and to ensure its immunogenicity and protective effectiveness it is necessary to maintain the cold chain. The objective of the study was to know about the structure and the process related to the cold chain in the vaccine rooms of municipalities in the Western Macroregion of the state of Minas Gerais. This is a descriptive epidemiologic study conducted in 253 vaccine rooms of the region. The results showed an inadequacy in structure and process of vaccine conservation that can damage the quality of immunobiologics. To ensure that the conservation of the vaccines is maintained since its manufacture until the use in health services requires, beyond the necessary equipment, technical knowledge of the professionals involved in the immunobiologics conservation process.